ELT in Covid-19-Augmented-Technological-Educational Ambience at the Private Universities in Bangladesh - Md. Nazmul Haque (English Department of Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to examine students’ obstacles encountered and the modifications they recommended in English language teaching and learning at private universities in Bangladesh during the COVID-19 pandemic. Applied mixed-method approach comprised of both qualitative and quantitative research methods. The findings of the study show that all participants go through virtual English language learning during the COVID-19 lockdown and the majority of them mention the difficulties to adopt a new approach in ELT suddenly, unstable network connection, costly internet data package, unskilled teachers, load shedding, mental stress, teachers’ and students’ lack of technological skills, not having technological devices and sense of remoteness as the prevailing disadvantages they face in online English language learning during COVID-19. This study also recommends that university authorities should train students and teachers concerning technological devices and uninterrupted internet network and power supply, high-speed internet, and fair assessment should be ensured. The prevalent result of the study is that online English language teaching and learning at private universities in Bangladesh require considerable pedagogical and technological modifications.